2022
DOI: 10.1021/acs.est.2c05280
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Metabolites and Particle Size Determine Cerium Oxide Nanomaterial Biotransformation

Abstract: Soil is a major receptor of manufactured nanomaterials (NMs) following unintentional releases or intentional uses. Ceria NMs have been shown to undergo biotransformation in plant and soil organisms with a partial Ce(IV) reduction into Ce(III), but the influence of environmentally widespread soil bacteria is poorly understood. We used high-energy resolution fluorescencedetected X-ray absorption spectroscopy (HERFD-XAS) with an unprecedented detection limit to assess Ce speciation in a model soil bacterium (Pseu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…Upon entering soil, CeO 2 NMs interact directly or indirectly with soil microorganisms, thereby affecting their metabolism. 35 It has been found that CeO 2 NMs underwent biotransformation in a microbial environment. 35 The electron extraction of Ce 4+ reduced to Ce 3+ can be used in the electron transport chain of cell energy production, thus changing the extracellular polymer of cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Upon entering soil, CeO 2 NMs interact directly or indirectly with soil microorganisms, thereby affecting their metabolism. 35 It has been found that CeO 2 NMs underwent biotransformation in a microbial environment. 35 The electron extraction of Ce 4+ reduced to Ce 3+ can be used in the electron transport chain of cell energy production, thus changing the extracellular polymer of cells.…”
Section: Resultsmentioning
confidence: 99%
“…35 It has been found that CeO 2 NMs underwent biotransformation in a microbial environment. 35 The electron extraction of Ce 4+ reduced to Ce 3+ can be used in the electron transport chain of cell energy production, thus changing the extracellular polymer of cells. 36 The extracellular and intracellular metabolites secreted by soil organisms are components of the soil metabolite pool.…”
Section: Resultsmentioning
confidence: 99%
“…However, the metabolism and excretion mechanisms of nanomedicines differ markedly from those of traditional drugs, potentially leading to accumulation within organisms and consequent long-term toxicity issues [123]. Furthermore, the size and surface characteristics of nanoparticles may influence their ability to navigate through hepatic, renal, or other excretory pathways, affecting not only the drug clearance rate but also the overall safety and efficacy of the therapeutic regimen [124]. the metabolism and excretion mechanisms of nanomedicines differ markedly from those of traditional drugs, potentially leading to accumulation within organisms and consequent long-term toxicity issues [123].…”
Section: Role Of Nanomedicine In Ndtmentioning
confidence: 99%
“…traditional drugs, potentially leading to accumulation within organisms and consequent long-term toxicity issues [123]. Furthermore, the size and surface characteristics of nanoparticles may influence their ability to navigate through hepatic, renal, or other excretory pathways, affecting not only the drug clearance rate but also the overall safety and efficacy of the therapeutic regimen [124]. Cisplatin Cl2H6N2Pt [114] In the domain of tumor therapy, nanomedicines predominantly operate through two major mechanisms: thermodynamics [125] and kinetics [126].…”
Section: Role Of Nanomedicine In Ndtmentioning
confidence: 99%
“…To date, many studies have demonstrated that NMs can regulate the composition and relative abundance of root exudates and the composition of rhizosphere microbial communities, thereby improving plant health. [13][14][15] However, most studies focused on plants with edible parts on the ground, and how NMs-mediated rhizosphere regulation affects the growth, development and productivity of rhizome crops remains largely unknown.…”
Section: Introductionmentioning
confidence: 99%